A world catalogue of Aholcocerus Yakovlev, 2006 (Lepidoptera, Cossidae) with description of a new species from Indonesia - Yakovlev, Roman V.; Witt, Thomas J. (Zootaxa, 2016)
Aholcocerus jakli Yakovlev & Witt sp. nov. is described from Indonesia. A catalogue of the genus Aholcocerus Yakovlev, 2006 is provided. External appearance of all species of the genus is illustrated.